2022
DOI: 10.1111/imig.13088
|View full text |Cite
|
Sign up to set email alerts
|

A critique of gender‐blind migration theories and data sources

Abstract: Despite this being the era of migration, no systematic theory of international migration has emerged, nor is there an academic or political agreement on ways in which migration is a ‘gendered’ process. Both theoretically and as inputs in the policy‐making process, gender‐blind approaches have actually rendered the gender dimension of migration more or less invisible. Through an in‐depth examination of the place of gender in the key theories of migration and relevant sources of data, the paper seeks to take sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…For example, it has been observed that gender as a socially constructed category is most often equated to women in qualitative studies (Fresnoza‐Flot & Shinozaki, 2017), a tendency resulting in the feminization of gender. In quantitative studies and statistical data on migration, Bircan and Yilmaz (2023) remark that gender has been used as synonymous with sex and that its ‘systematic integration’ in ‘migration theory and policy has yet to materialise’ (p. 174). They propose an alternative way to treat gender in migration statistics by developing ‘quantitative as well as qualitative indicators to monitor the gender dimension of migration’ (p. 181).…”
Section: Valuing Critical Reflexivitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been observed that gender as a socially constructed category is most often equated to women in qualitative studies (Fresnoza‐Flot & Shinozaki, 2017), a tendency resulting in the feminization of gender. In quantitative studies and statistical data on migration, Bircan and Yilmaz (2023) remark that gender has been used as synonymous with sex and that its ‘systematic integration’ in ‘migration theory and policy has yet to materialise’ (p. 174). They propose an alternative way to treat gender in migration statistics by developing ‘quantitative as well as qualitative indicators to monitor the gender dimension of migration’ (p. 181).…”
Section: Valuing Critical Reflexivitymentioning
confidence: 99%
“…Gender and migration research is taking this direction step‐by‐step starting with the identification of critical issues in the field, namely the frequent equation of gender with women in qualitative studies and with sex in quantitative research and statistical data. The next logical step will be to delve into these issues and produce sufficient data on gender and migration that can influence societal actors and policymaking at the macro level (see Bircan & Yilmaz, 2023), and third, at the intersection of gender studies and migration studies, the research field of gender and migration offers a wide space for theoretical, methodological and policy reflections through the prism of an intersectional approach, 2 the adoption of a reflexive stance or the combination of these frames. Hence, it offers an intermediary ground to gender studies and migration studies where fairness and equity can be fully realized in both scholarly and societal terms.…”
Section: Conclusion: Towards An Intersectional and Reflexive Research...mentioning
confidence: 99%
“…However, the interpretation of what constitutes big data varies considerably among different scientific areas, including studies of human migration and mobility. Hence, before examining how big data enhances or is applied in existing data sets concerning human movement, it is crucial to clarify the notion of big data both in the context of human migration and more broadly (Bircan et al, 2023).…”
Section: Definitions and Problem Presentationmentioning
confidence: 99%
“…In the absence of detailed data on migrants, many aspects of international migration remain understudied, and countries cannot exploit the many benefits of migration (Clemens, 2014). Additionally, the existing international migration data are subject to significant gaps and deficiencies (Bircan et al, 2020). These gaps fall into five conceptual categories – namely, inconsistent definitions, scant information on the reasons driving migration decisions, uneven geographic coverage, missing information on the demographic characteristics of migrants and outdated (obsolete) data (Ahmad-Yar and Bircan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These sex-specific migration data provided by the UN Population Division became available to the public in 2002 (Boyd, 2021). Gender statistics are necessary for thorough gender analyses, however, sex-disaggregated data are the best alternative at this stage and an essential first step toward gender statistics but they come with availability and quality issues (Bircan & Yilmaz, 2022).…”
Section: What Are the Differences In Labor Market Discrimination Base...mentioning
confidence: 99%